THE INTERACTION BETWEEN PERSONALITY TRAITS AND CONTEXTUAL DISADVANTAGE ON CRIMINAL BEHAVIOR: A LONGITUDINAL STUDY OF HIGH RISK-FEMALES - Gudonis, Lauren C. (2009)
This investigation examined several dimensions of personality functioning in a longitudinal sample of females. These data are part of an existing project evaluating female development across 3 different time points starting in adolescence and transitioning into adulthood. Subjects were categorized into a clinical group (females with a high degree of psychiatric comorbidity) and a normal control group. All participants were initially recruited when they were between 14-18 years of age, and were followed up twice when they were 19-23, and 24-28. In an attempt to explore possible heterogeneity in personality trait development, the research is presented as three separate studies examining the following: (1) fluctuations in mean-level and rank order stability estimates across time; (2) the validity of established personality trends relative to their association with antisocial behavior; and (3) mechanisms that may contribute to personality trait consistency across development such as neighborhood context. This is the first study to investigate personality functioning across time in females who are disturbed in multiple areas of social and psychological functioning. Results highlight the importance of considering distinct subgroups of the general population when exploring developmental trends in personality